Storage time and quality of garlic, amarante cv - Carvalho, Vania Déa de; Souza, Sára Maria Chalfoun de; Abreu, Celeste Maria Patto de; Chagas, Sílvio Julio de Rezende (Pesquisa Agropecuaria Brasileira, 1991)
The objective of this work was to determine the effect of storage time on garlic (Allium sativum) cv. Amarante bulb quality. Weight lost, total solids, piruvic acid, titratable acidity, essential oil and industrial index values of garlic (Allium sativum) cv. Amarante at 0, 30, 60, 90, 120 and 150 days of post-harvest storage period. Pyruvic acid, titratable acidity and weight lost values of bulbs increased and total solids decreased with post-harvest storage. The best essential oil values were obtained at 0 and 120 post-harvest storage days. The best time period to obtain the highest values of industrial index was 60 to 120 days of post-harvest storage.